Inkjet-printed micro-calibration standards for ultraquantitative Raman spectral cytometry. Issue 12 (22nd May 2019) - LaLone, Vernon; Fawaz, Maria V.; Morales-Mercado, Jomar; Mourão, Márcio A.; Snyder, Catherine S.; Kim, Sang Yeop; Lieberman, Andrew P.; Tuteja, Anish; Mehta, Geeta; Standiford, Theodore J.; Raghavendran, Krishnan; Shedden, Kerby; et al.
Abstract : Picogram-scale biomolecule standards enable calibration. Abstract : Herein we report the development of a cytometric analysis platform for measuring the contents of individual cells in absolute (picogram) scales; this study represents the first report of Raman-based quantitation of the absolute mass – or the total amount – of multiple endogenous biomolecules within single-cells. To enable ultraquantitative calibration, we engineered single-cell-sized micro-calibration standards of known composition by inkjet-printer deposition of biomolecular components in microarrays across the surface of silicon chips. We demonstrate clinical feasibility by characterizing the compositional phenotype of human skin fibroblast and porcine alveolar macrophage cell populations in the respective contexts of Niemann–Pick disease and drug-induced phospholipidosis: two types of lipid storage disorders. We envision this microanalytical platform as the foundation for many future biomedical applications, ranging from diagnostic assays to pathological analysis to advanced pharmaco/toxicokinetic research studies.